Dampak Kepemilikan Keris Bagi Botoh Samin di Kudus Jawa Tengah - Moh Rosyid (Universitas Tanjungpura, 2021)
This article discussed the goal of impact keris for Samin pioneer (botoh). Data collection done by interview, observation, and literature was analyzed using a qualitative descriptive approach. As the result, Keris is magical objects owned by a certain person in between pioneer Samin in Kudus inheritance from ancestors. Ancestral pioneer Samin message Keris to help by magic treatment and stay a way from arrogant nature. Keris encourage to be brave in their dynamic life. Negative effect came from it if not well controlled will make the owner have an arrogant habit. There are value on the benefits at keris as medium traditional treatment for Samin community.